TINGKAT PENDIDIKAN, PEMAHAMAN AKUNTANSI, SKALA USAHA, DAN LAMA USAHA TERHADAP KUALITAS LAPORAN KEUANGAN UMKM - Novia'atul Aullah; Umi Nandiroh; Dwiyani Sudaryanti (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2022)
Abstract: Micro, Small and Medium Enterprises (MSMEs) play an important role in upholding the country's economy. Thus, every MSME actor is expected to be able to produce quality financial reports. Because financial reports are able to analyze the financial performance of an entity. This study aims to determine the effect of education level, understanding of accounting, business scale, and length of business on the quality of financial reports. This study used purposive sampling as a technique in taking the sample. as many as 90 questionnaire data for MSME actors were processed with SPSS 25.0 for windows. In this study it was concluded that there was a partial influence between the variables of education level, accounting comprehension reports, business scale on financial quality. But in this study did not find any significant effect between the length of business variables on the quality of financial reports.